Analysis of the knowledge of nursing and medical academic students about organ donation (Research, Society and Development, 2022)
The objective of this study was to describe and analyze the sociodemographic profile and the main perceptions of university students in Nursing and Medicine courses at a Brazilian public university about organ donation. This is a cross-sectional and descriptive study, with a qualitative-quantitative approach. The data collection instrument was an online questionnaire, self-administered and adapted from a previous study. The software used for the tabulation and organization of the data was Microsoft Excel 2016, and for the statistical analysis, the Statistical Package for Social Sciences, version 26, was used. The sample consisted of 236 students, 122 of them from the nursing course and 114 from medicine. Regarding gender, in medicine there was a small predominance of male individuals (55.4%), while in nursing there was a predominance of women (72.7%). Among the main reasons given by the participants for refusing to donate organs after death, is insufficient knowledge of the subject, followed by insecurity. Among the participants who answered that they would not be donors in a living transplant, the predominant reason for refusal was insecurity or fear. Half of the participants answered that they did not know if the subject is part of their undergraduate curriculum and approximately 80% reported that they had never participated in any extracurricular activity related to organ donation. The findings of this study demonstrated the inadequacy of organ donation training among students. Academics do not have sufficient access to this knowledge within the university, culminating in a professional training deficit.